A Highly Efficient Nanomaterial with Molecular Imprinting Polymer: Carbon Nitride Nanotubes Decorated with Graphene Quantum Dots for Sensitive Electrochemical Determination of Chlorpyrifos. Issue 6 (1st January 2017) - Yola, Mehmet Lütfi; Atar, Necip
Abstract : Chlorpyrifos (CHL) is organophosphate insecticide and has low water solubility (1.39 mg/L). CHL is known to produce toxic effects by inhibiting the acetylcholinesterase enzyme activity. Because of this, the important health problems occur worldwide. Hence, it is important to detect the concentration of CHL at the sensitive levels in environmental waters. In this study, a novel molecular imprinted voltammetric sensor based on carbon nitride nanotubes (C3 N4 NTs) decorated with graphene quantum dots (GQDs) modified glassy carbon electrode (GCE) was developed for determination of CHL. The unique C3 N4 NTs@GQDs nanohybrid was synthesized by hydrothermal treatment. CHL imprinted GCE based on C3 N4 NTs@GQDs nanohybrid was prepared via electropolymerization process of 100 mM pyrrole as monomer in the presence of phosphate buffer solution (PBS) (pH 7.0) containing 25 mM CHL. The prepared nanomaterials were characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), raman spectroscopy, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) and X-ray photoelectron spectroscopy (XPS). The linearity range and the detection limit of the method were calculated as 1.0 × 10 −11 –1.0 × 10 −9 M and 2.0 × 10 −12 M, respectively. The sensor was applied to wastewater samples with good selectivity and recovery. The stability and selectivity of the voltammetric sensor were also reported.